Peran Pendidikan dan Ilmu Pengetahuan di Era Digital dalam Perspektif Berpikir Kritis Norman Fairclough - Retnosari, Putri; Imawati, Endah (Jurnal Pena Indonesia, 2024)
The research with the title “The Role of Education and Science in the Digital Age in theperspective of Norman Fairclough's Critical Thinking Teaching” is motivated by the challengesfaced by the world of education and science in the increasingly complex digital era, which is notonly in the form of competition for express teaching models, but also human interest in falsetruths and information. The critical thinking teaching method offered by Fairclough opens newhorizons for the world of education and science so as not to be trapped by offers ofsophistication and sophistication alone, because developments in the digital era are alsorealized to have a negative impact on humans. This research is qualitative research using theliterature method. The formal object in this research is Norman Fairclough's critical thinkingteaching method, while the material object used in this research is the basic concept ofeducation and science. After conducting a search in this study, the results obtained are (1) theformulation of critical thinking on the concepts of education and science (2) finding the role ofeducation and science of education in the digital era by involving five basic concepts initiatedby Fairclough, namely action, context, history, power and ideology.